2009
DOI: 10.3340/jkns.2009.45.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Hemifacial Spasm Caused by Epidermoid Tumor at Cerebello Pontine Angle

Abstract: Hemifacial spasm (HFS) is almost always induced by vascular compression but in some cases the cause of HFS are tumors at cerebellopontine angle (CPA) or vascular malformations. We present a rare case of hemifacial spasm caused by epidermoid tumors and the possible pathogenesis of HFS is discussed. A 36-year-old female patient presented with a 27-month history of progressive involuntary facial twitching and had been treated with acupuncture and herb medication. On imaging study, a mass lesion was seen at right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…[8] As for HS induced by benign tumors in many cases, as in our patient, previous researchers suggested that the vascular compression under the tumor is the main cause of the HS. [9,10] Typical MRI appearance of an epidermoid tumor is hypo to slight hyperintense on T1W images, iso to hyperintense on T2W images, and hyperintense on DWI. [11,12] Arachnoid cysts and schwannomas also appear as hyperintense on T1W images and hyperintense on T2W images.…”
Section: Discussionmentioning
confidence: 99%
“…[8] As for HS induced by benign tumors in many cases, as in our patient, previous researchers suggested that the vascular compression under the tumor is the main cause of the HS. [9,10] Typical MRI appearance of an epidermoid tumor is hypo to slight hyperintense on T1W images, iso to hyperintense on T2W images, and hyperintense on DWI. [11,12] Arachnoid cysts and schwannomas also appear as hyperintense on T1W images and hyperintense on T2W images.…”
Section: Discussionmentioning
confidence: 99%
“…Offending vessels are most often found on preoperative radiologic evaluation or during surgery; MVD of these offending vessels has yielded successful outcomes in large serial studies 1 , 8) . In several rare secondary causes of HFS, including CPA tumors, aneurysms, and AVMs, compression of the facial nerve REZ by altered vasculature is also considered the etiology of HFS 5 , 7 , 10 , 13 , 17 , 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of HFS is not yet well established, vascular compression of the facial nerve root exit zone (REZ) is one likely mechanism given the effectiveness of microvascular decompression (MVD) in the treatment of the disorder 1 , 7 , 9) . Moreover, the vascular compression theory has been accepted as the etiology of rare secondary HFS in some cases of cerebellopontine angle (CPA) tumors, aneurysms, and arteriovenous malformations (AVMs) 5 , 7 , 10 , 13 , 17 , 18) . However, another theory for the mechanism of HFS, hyperexcitability of the facial nucleus, has also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Among 2050 HFS patients, CPA tumors were detected in 9 (0.4%) and 2 of them were epidermoids. [ 6 ]…”
mentioning
confidence: 99%
“…[ 4 ] Recently, arterial compression at the root exit zone was also reported in the majority of HFS cases with CPA epidermoids. [ 5 6 ]…”
mentioning
confidence: 99%